The Mammalian Target of Rapamycin and DNA methyltransferase 1 axis mediates vascular endothelial dysfunction in response to disturbed flow. Issue 1 (December 2017) - Zhang, Yun-Peng; Huang, Yi-Tao; Huang, Tse-Shun; Pang, Wei; Zhu, Juan-Juan; Liu, Yue-Feng; Tang, Run-Ze; Zhao, Chuan-Rong; Yao, Wei-Juan; Li, Yi-Shuan; Chien, Shu; Zhou, Jing
Abstract The earliest atherosclerotic lesions preferentially develop in arterial regions experienced disturbed blood flow, which induces endothelial expression of pro-atherogenic genes and the subsequent endothelial dysfunction. Our previous study has demonstrated an up-regulation of DNA methyltransferase 1 (DNMT1) and a global hypermethylation in vascular endothelium subjected to disturbed flow. Here, we determined that DNMT1-specific inhibition in arterial wall ameliorates the disturbed flow-induced atherosclerosis through, at least in part, targeting cell cycle regulator cyclin A and connective tissue growth factor (CTGF). We identified the signaling pathways mediating the flow-induction of DNMT1. Inhibition of the mammalian target of rapamycin (mTOR) suppressed the DNMT1 up-regulation bothin vitro andin vivo . Together, our results demonstrate that disturbed flow influences endothelial function and induces atherosclerosis in an mTOR/DNMT1-dependent manner. The conclusions obtained from this study might facilitate further evaluation of the epigenetic regulation of endothelial function during the pathological development of atherosclerosis and offer novel prevention and therapeutic targets of this disease.